PENGARUH AUDIT PAJAK DAN KEPATUHAN WAJIB PAJAK TERHADAP PENINGKATAN TAX RATIO DI KANTOR PELAYANAN PAJAK TANGERANG SELATAN - Mahwiyah, Mahwiyah; Khotimah, Husnul; Betara, Santika (JURNAL LENTERA AKUNTANSI, 2023)
The purpose of this study was to determine the effect of tax audits and taxpayer compliance with the Tax Ratio at the South Tangerang Primary Tax Office. In this study using a quantitative approach with data techniques using a questionnaire. The scale of data measurement with a Likert scale. Data were analyzed using multiple regression analysis with the help of the SPSS version 25 program. The results showed that the Tax Audit variable has a significance level of 0.045. The sig value of 0.045 is smaller than 0.05 and the t-count value of 2.041 is greater than the t-table value of 1.6637. So it can be interpreted that the Tax Audit variable has a positive and significant effect on the Increase in Tax Ratio. The Taxpayer Compliance variable has a significance level of 0.007. The sig value of 0.007 is smaller than 0.05 and has a t-count value of 2.756 which is greater than the t-table value of 1.6637 and can be interpreted as Taxpayer Compliance which turns out to have a positive and significant effect on increasing the Tax Ratio. Based on the research results, it is expected that KPP Pratama South Tangerang can maximize the implementation of tax audits so that taxes and tax revenues increase and are expected to be able to conduct counseling and outreach aimed at increasing taxpayers.Key words: Tax Audit, Tax Payer Compliance, Tax Ratio